Isolation and identification of lactic acid bacteria from ginseng sprouts and research on their probiotic, anti-inflammatory, and anti-cancer activity - Lee, JeongOk; Jung, Selin; Lee, Ji-Eun; Hamayun, Muhammad; Park, Su Hwan; Choi, Young-Jin; Kim, Eun-Kyung; Lee, Jong-Ho; Kim, Ho-Youn; Lee, Bokyung (Frontiers in Nutrition, 2026)
IntroductionGinseng sprouts are recognized as a potentially valuable food source as they provide an abundance of bioactive compounds with antioxidants and anti-cancer properties. This study investigates the probiotic properties of lactic acid bacteria (LAB) from ginseng sprouts, addressing gaps in plant-based probiotic discovery.MethodsA total of 17 putative LAB strains were obtained from 688 bacterial isolates from ginseng sprouts. Molecular identification via 16S rRNA sequencing classified and selected five isolates as LAB taxa. Their probiotic potential was evaluated through in vitro assays assessing gastrointestinal stress tolerance (pH 3.0 and 0.3% bile salt), antibacterial activity, safety, and antioxidant activity (DPPH scavenging), anti-inflammatory (TNF-α secretion), and cancer cell cytotoxicity (WST-8 assay and apoptosis induction).ResultsAfter 16S rRNA sequencing, five candidate probiotic strains from ginseng sprouts were identified, including three strains of Lacticaseibacillus rhamnosus (B7112, B3402, and B3421), one strain of Leuconostoc lactis (B34171), and one strain of Leuconostoc mesenteroides (B22051). In vitro assays evaluating their probiotic potential revealed that all five strains exhibited robust tolerance to acidic pH and the presence of bile salts, notable antibacterial activity, antibiotic susceptibility, and strong adhesion to intestinal epithelial cells. Notably, these LAB isolates demonstrated DPPH radical scavenging activity comparable to that of 25 μM L-ascorbic acid, indicating significant antioxidant capacity. Furthermore, quantitative RT-PCR analysis showed that these LAB strains significantly downregulated TNF-α mRNA expression, reflecting substantial anti-inflammatory effects. In addition, protein extracts derived from LAB strains effectively inhibited cancer cell proliferation in vitro.ConclusionThese findings highlight the therapeutic promise of plant-derived probiotic bacterial strains for potential applications in human health, particularly in inflammation and cancer prevention. Moreover, the successful isolation of probiotic LAB from ginseng sprouts underscores the potential of ginseng as a valuable source of health-promoting microbiota.